Case Report: Giant cystic solid aggressive fibromatosis of the pancreas: clinical and pathologic features - Feng, Runlin; Zhang, Tao; Feng, Lijuan; Tao, Yanping; Wang, Jiaping (Frontiers in Oncology, 2025)
BackgroundAggressive fibromatosis is a rare and aggressive soft tissue tumor. The pathologic histomorphology is varied and characterized by fibroblast and myofibroblast differentiation. Aggressive fibromatosis can be classified into extra-abdominal, abdominal wall, and intra-abdominal types. The abdominal wall type is the most common, while originating from the pancreatic region is extremely rare. Therefore, we report a case of a patient with a diagnosis of giant cystic solid aggressive fibromatosis of the pancreas.Case summaryThe patient was a 39-year-old woman who was admitted to the hospital because of left upper abdominal pain that persisted for 20 days. She was in relatively good health with no history of previous illnesses. No additional abnormal manifestations were noted on physical examination. Laparoscopic pancreatic body and tail combined splenectomy was performed under general anesthesia. The postoperative pathologic diagnosis was pancreatic aggressive fibroma. No disease recurrence was observed during the postoperative follow-up period.ConclusionThe primary pancreatic aggressive fibroma is very rare. The clinical presentation lacks specificity, and imaging findings are not quite typical. The definitive diagnosis relies on postoperative pathology and immunohistochemistry. Complete surgical resection is the treatment of choice when possible. Due to its aggressive behavior, regular follow-up is required.